Age-Related Trends of Patients Undergoing Thyroidectomy: Analysis of US Inpatient Data from 2005 to 2013. (March 2019) - Echanique, Kristen A.; Govindan, Aparna; Mohamed, Omar M.; Sylvester, Michael; Baredes, Soly; Yu-Lan Ying, Mary; Kalyoussef, Evelyne
Objectives: As the country ages, thyroidectomies can be expected to be performed more frequently among the elderly. In this study, we stratified patients by age to explore demographics and complications of patients undergoing thyroidectomy. Study Design: Retrospective study with a national database. Setting: Nationwide Inpatient Sample. Subjects and Methods: A total of 414, 079 thyroidectomy cases from 2005 to 2013 were identified. Complications, outcomes, demographics, length of stay, and hospital charges were evaluated among patients and stratified by age into 4 cohorts: younger (<65 years), advanced age (65-74 years), elderly (75-84 years), and superelderly (≥85 years). Results: Of 414, 079 thyroidectomy cases identified, patients aged <65 years accounted for 75.6% of cases, while those aged 65-74, 75-84, and ≥85 years accounted for 16.3%, 7.2%, and 0.9%, respectively ( P < .001). There was a significant difference in length of stay, total hospital charges, and mortality throughout the different age groups ( P < .001), all trending upward with advancing age. In the aging population, incidence of recurrent laryngeal nerve injury, transfusion of erythrocytes, and acute cardiac complications increased with increasing age ( P < .001), while hypoparathyroidism decreased with age ≥65 but ≤85 years ( P < .001). Patients aged ≥75 years had increased odds of mortality as compared with their younger counterparts ( P < .001). Conclusion: This study utilized a national database to describe and elucidate trends in older populations undergoing thyroidectomy. Thyroid-related complications, including blood transfusion and recurrent laryngeal nerve injury, increased with increasing patient age. This information will help to guide pre- and postoperative care for aging patients undergoing thyroidectomy.